Reimagining Mantenan: The Changing Traditions of Javanese Marriages in Panglungan Village, East Java - Perdana, Ahmad Sahrul Febriansah; Ainiyah, Qurrotul (IAIN Manado, 2025)
This research explores the transformation of the mantenan tradition in Panglungan Village, East Java, as it adapts to social, religious, and cultural changes in modern times. Mantenan, a traditional Javanese marriage ceremony, is deeply embedded in cultural values and rituals such as Nontoni, Lamaran, Tembusan, Petung, Adeg Tratag, Pasang Tarub, Kembar Mayang, Siraman, Midodareni, Ijab and Qabul, Temu Manten, and Walimahan. Using an ethnographic approach, this study examines how these rituals, rich in symbolism and spirituality, continue to evolve in response to modernization and shifting community structures. Through Geertz's trichotomy theory, the research reveals how the Panglungan community reimagines these rituals, adapting them to contemporary values while preserving their cultural identity. The findings demonstrate how the tradition of mantenan has been reinterpreted to maintain its relevance in the modern era, ensuring the continuity of ancestral heritage while reinforcing the unique cultural identity of the Javanese people of Panglungan. This study also highlights the dynamic nature of cultural traditions and their role in shaping community identity in the face of modernity.